SOCIOPRAGMATIC ANALYSIS OF THE TRANSFORMATION OF SIMPLE SENTENCES INTO DIFFERENT SPEECH FORMS - Djamalutdinova Barno Ramizitdinovna (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This thesis examines the issues of how simple sentences change and adapt in different speech forms (formal, informal, academic, literary and everyday communication) from a sociopragmatic perspective. Simple sentences are considered the simplest and most basic units of language, but they are transformed in various ways under the influence of social context, cultural norms and communicative goals. The thesis analyzes how simple sentences are transformed in different speech forms, under what socio-pragmatic factors they are formed, and the role of language in expressing social dynamics. The results of the study show that the flexibility of simple sentences allows us to understand the important role of language in social life and how it can change in different contexts.